The Benefits of Planting Edible Plants Amidst The Pandemic - Mobo, Froilan D.; Garcia, Ana Liza (Future Science / FSH-PH Publications, 2022)
Incarcerated at home or what we call in layman’s term as “house arrest” is what happened to all of us during the pandemic as it hits from 15th of March in the year 2020. People are forced to stay in their own dwellings to keep everybody safe and be away from any contact to anyone that might be carrying the silent presence of the virus covid-19. Since then, people was able to utilize and exert all efforts to do the things that they are not doing or was not even their choice of doing prior to covid-19 when all is carefree living their own lives. One of which is gardening that spreads throughout the world as contagious as anyone’s sweet smile. People began to consider its importance and benefits of planting your own crops in your own backyard using whatever you got around your perimeter. Aside from the obvious reason that people are obliged to stay at home until the Alert Level was down to the safest status of the virus. We are one of those who did indulged ourselves in planting our own vegetables and I would say that it was so fulfilling and the feeling of being like a co-creator of the Almighty for recreation of these beneficial living things.